Meta-analysis of delayed gastric emptying after pylorus-preserving versus pylorus-resecting pancreatoduodenectomy. Issue 4 (7th February 2018) - Klaiber, U.; Probst, P.; Strobel, O.; Michalski, C. W.; Dörr-Harim, C.; Diener, M. K.; Büchler, M. W.; Hackert, T.
Abstract: Background: Delayed gastric emptying (DGE) is a frequent complication after pylorus-preserving pancreatoduodenectomy. Recent studies have suggested that resection of the pylorus is associated with decreased rates of DGE. However, superiority of pylorus-resecting pancreatoduodenectomy was not shown in a recent RCT. This meta-analysis summarized evidence of the effectiveness and safety of pylorus-preserving compared with pylorus-resecting pancreatoduodenectomy. Methods: RCTs and non-randomized studies comparing outcomes of pylorus-preserving and pylorus-resecting pancreatoduodenectomy were searched systematically in MEDLINE, Web of Science and CENTRAL. Random-effects meta-analyses were performed and the results presented as weighted odds ratios (ORs) or mean differences with their corresponding 95 per cent confidence intervals. Subgroup analyses were performed to account for interstudy heterogeneity between RCTs and non-randomized studies. Results: Three RCTs and eight non-randomized studies with a total of 992 patients were included. Quantitative synthesis across all studies showed superiority for pylorus-resecting pancreatoduodenectomy regarding DGE (OR 2·71, 95 per cent c.i. 1·48 to 4·96; P = 0·001) and length of hospital stay (mean difference 3·26 (95 per cent c.i. −1·04 to 5·48) days; P = 0·004). Subgroup analyses including only RCTs showed no significant statistical differences between the two procedures regarding DGE, and for all other effectiveness and safety measures. Conclusion: Pylorus-resecting pancreatoduodenectomy is not superior to pylorus-preserving pancreatoduodenectomy for reducing DGE or other relevant complications.